Control of temperature and aqueous Mg2+/Ca2+ ratio on the (trans-)formation of ikaite. (15th November 2017) - Purgstaller, B.; Dietzel, M.; Baldermann, A.; Mavromatis, V.
Abstract: The calcium carbonate hexahydrate mineral ikaite (CaCO3 ⋅ 6 H2 O) has been documented in aquatic environments at near-freezing temperatures. An increase of the prevailing temperature in the depositional environment, results in the transformation of natural ikaite into less soluble calcium carbonate phases occasionally leaving calcite pseudomorphs in the sediments, which are considered as an indicator for primary cold water temperatures. Detailed understanding on the physicochemical parameters controlling ikaite (trans-)formation however, such as temperature and reactive solution chemical composition, are still under debate. In order to study the formation of ikaite, we conducted precipitation experiments under controlled physicochemical conditions (pH = 8.3 ± 0.1; T = 6, 12, and 18 ± 0.1 °C) at defined aqueous molar Mg/Ca ratios. The transformation of ikaite into anhydrous calcium carbonate polymorphs was investigated in solution and at air exposure. The obtained results reveal the formation of ikaite at temperatures up to 12 °C, whereas Mg-rich amorphous calcium carbonate precipitated at 18 °C. In contact with the reactive solution ikaite transformed into aragonite at aqueous molar Mg 2+ /Ca 2+ ratios of ≥14. In contrast, ikaite separated from the Mg-rich solution and exposed to air transformed in all cases into calcite/vaterite. The herein obtained temperature limit of ≤12 for ikaite formation is significantly higher than formerly expected and most probably caused by (i) the high saturation degree of the solution with respect to ikaite and (ii) the slow dehydration of the aqueous Ca 2+ ion at low temperatures. This result questions the suitability of calcite pseudomorphs (i.e. glendonites) as a proxy for near-freezing temperatures. Moreover, our findings show that the CaCO3 polymorph formed from ikaite is strongly controlled by the physicochemical conditions, such as aqueous molar Mg 2+ /Ca 2+ ratio of the reactive fluid and H2 O availability throughout the transformation process.